PERBANDINGAN PENGIRIMAN TEKS, GAMBAR, DAN SUARA MENGGUNAKAN KOMUNIKASI LoRa - Taufik Hendarto; Hamid Azwar (ABEC Indonesia, 2021)
This Long Range communication technology is widely used as a substitute for LTE communication tools, but sending text, images, and voice in Long Range communication has a different performance ratio of transmission time speed. This tool uses two TTGO ESP32 LoRa modules, the tools used to design the application using the MIT App Invertor and an additional device, a USB OTG cable. The way this tool works is to send text, image and voice messages without using a server but using point-to-point communication between two devices. The test results of sending text, images, and voice on Long Range communications that have been carried out in data loss testing conditions, show that the results of sending text messages, the farther the distance, the delivery speed is relatively stable with a delay of 1.2 seconds, while for sending images the delay results are getting bigger which is 3.9 seconds and for voice transmission it is not very compatible because LoRa devices can only send 256 bytes of data packets.   Keywords: Pesan Teks, Gambar, Suara, App Inventor, TTGO ESP32 LoRa.